Condition of Renal Excretory Function in Patients with Chronic Liver Diseases - Kvasnytska, O.; Gozhenko, A.; Zukow, W. (Journal of Education, Health and Sport, 2024)
This study examined 37 patients with hepatitis and cirrhosis of the liver and 30 healthy individuals, assessing liver function indicators and renal function under conditions of daily diuresis and after a load of drinking water and a 0.5% sodium chloride solution, at 0.5% of body weight. The study showed that hepatitis and cirrhosis of the liver lead to signs of hepatorenal syndrome development, particularly in patients with cirrhosis, primarily manifested by a reduction in glomerular filtration rate (GFR). The extent of reduction correlated with the severity of liver damage. Simultaneously, it was independent of blood pressure, plasma protein, and renal sodium exchange mechanisms. The primary dysfunction in hepatorenal syndrome was determined to be a reduction in GFR, evidenced by the rise in creatinine concentration, although urea increased only in cirrhosis, requiring further explanation. The results showed that liver diseases, especially cirrhosis, can lead to kidney problems, mainly by reducing the kidney's ability to filter blood, which was shown by higher creatinine levels in the blood.